2017
DOI: 10.1631/fitee.1700053
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid-augmented intelligence: collaboration and cognition

Abstract: The long-term goal of artificial intelligence (AI) is to make machines learn and think like human beings. Due to the high levels of uncertainty and vulnerability in human life and the open-ended nature of problems that humans are facing, no matter how intelligent machines are, they are unable to completely replace humans. Therefore, it is necessary to introduce human cognitive capabilities or human-like cognitive models into AI systems to develop a new form of AI, that is, hybrid-augmented intelligence. This f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(83 citation statements)
references
References 97 publications
0
80
0
3
Order By: Relevance
“…Zheng et al assert that the long-term goal of AI is to enable machines to think like humans. Therefore, the question remains, can any computer truly replace the function of the human mind [62]?…”
Section: Ai Vs Iamentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al assert that the long-term goal of AI is to enable machines to think like humans. Therefore, the question remains, can any computer truly replace the function of the human mind [62]?…”
Section: Ai Vs Iamentioning
confidence: 99%
“…Furthermore, AI is not suited for situations where end goals and inputs are not well defined, thereby prompting IA to play a crucial role [60]. This is further explored by Zheng et al [62], who argue that owing to high levels of uncertainties and vulnerabilities in human life, machines are unable to completely replace humans. Interestingly, They propose the concept of human-in-the-loop augmented intelligence through human-computer collaboration.…”
Section: Ai Vs Iamentioning
confidence: 99%
“…We propose that this role could be best realized through cooperative synergy between a data-driven analytics system focused on computational analysis and a user capable of making personally relevant interpretations and focusing on the qualitative aspects of social matching. us, ICT-enhanced social serendipity could be aimed at achieving human-in-the-loop analytics [69] and augmented intelligence [70,71] rather than artificial intelligence, that is, supplementing human intelligence with computational capabilities through new forms of HCI. e innate differences between human decision-making and computational logic necessitate careful design of the interplay of these two types of intelligence [72].…”
Section: Encouragement and Persuasiveness For Value Creation And Mainmentioning
confidence: 99%
“…Kuo et al [124] showed that the neurons in the insula and anterior cingulate cortex of the brain are more active during intuitive reasoning, wheras the median, inferior parietal, and anterior torso are more active in logical reasoning, demonstrating the independence of intuition and logical reasoning systems from the perspective of neuroscience. Zheng et al [125] also pointed out that a human's intuitive reasoning is closely related to the abstract ability and strong generation ability of the human brain to prior knowledge, rather than simple mechanical memory. It was further pointed out that human intuition can rapidly allow decisions to be made with regard to risk avoidance based on the world model of the human brain owing to this high degree of generalization.…”
Section: Intuitive Reasoning For Traffic Situation Understanding Basementioning
confidence: 99%
“…It was further pointed out that human intuition can rapidly allow decisions to be made with regard to risk avoidance based on the world model of the human brain owing to this high degree of generalization. The authors [125] also provided a basic method of computational realization of intuitive reasoning. In conclusion, it is insufficient to rely on logical reasoning for autonomous vehicles to drive in open traffic scenarios, and intuitive reasoning must therefore be introduced into the computing framework of self-driving cars.…”
Section: Intuitive Reasoning For Traffic Situation Understanding Basementioning
confidence: 99%